Nitrogen dynamics in runoff from two small heathland catchments representing opposite extremes with respect to climate and N deposition in Norway - Kaste, Ø.; Skjelkvåle, B. L. (Hydrology and Earth System Sciences, 2002)
Effects of contrasting climatic conditions and nitrogen (N) deposition levels on streamwater N dynamics are assessed at two small heathland catchments; Dalelva in northern Norway (69°N) and Øygard in southwestern Norway (58°N). The study comprises 11 years of data on climate, hydrology and N inputs/outputs from Dalelva and 8 years of corresponding data from Øygard. Both sites are comparable in catchment size, geology and land cover characteristics, but have large differences in climate and N deposition. Dalelva is characterised by a cold, arctic climate and low N deposition (2-3 kg N ha–1y–1), whereas the Øygard site has a more mild, humid climate with much larger N deposition (13–19 kg N ha–1yr–1). Streamwater nitrate (NO3‾) concentrations at Dalelva generally were negligible during the growing season, but showed a steady increase during the dormant season until a maximum of 40-100 μg N L–1 was reached just before snowmelt. At onset of the snowmelt flood, NO3‾ concentrations decreased momentarily to very low levels, suggesting that N eluted from the seasonal snowpack to a great extent was infiltrated and immobilised in the soils. At Øygard, flood peaks occurred frequently during all seasons, and usually there was no distinct spring flood. A lack of clear dilution effects from floods on streamwater N3‾ concentrations may indicate a relatively high NO3‾ leaching potential in this catchment. On average, the annual NO3– export was negligible at Dalelva (<0.1 kg N ha–1yr–1), while at Øygard it amounted to 3.0±0.3 (±1 s.d.) kg ha–1yr–1, or nearly 20% of the annual N deposition. In addition to this relatively high annual N loss, elevated NO3‾ concentrations during the growing season further indicate that the N supply at Øygard is in excess of the combined plant and microbial demand. Keywords: catchments, surface water, nitrogen deposition, nitrate leaching, climate, hydrology, snowmelt, Dalelva brook, Øygard brook